2022
DOI: 10.1002/anie.202208290
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Induced Symmetry Conversion of DNA Origami Lattices

Abstract: DNA nanotechnology has provided credible approaches for assembly of three-dimensional (3D) lattices with complex patterns. However, the symmetries are strictly dependent on their initial configurations and difficult to alter via non-thermal treatments. While switchable nucleic acid structures have been employed to construct deformable DNA motifs, it remains challenging to arrange them anisotropically in 3D lattices to trigger directed collective shape transition and dynamic symmetry conversion. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…There are also many other strategies to induce dynamic structural changes, including molecular recognition, such as aptamer binding, hybridization, and dehybridization of nucleic acid duplexes, environmental factors such as pH value, temperature, , light, , and ionic concentration, and enzymatic reactions to DNA strands, such as strand degradation, cleavage, ligation, and extension . Specifically designed DNA sequences can enable DNA structural changes regulated by metal ions or pH. , Base stacking between blunt ends of DNA helices is sensitive to metal ions and temperature and has also been utilized to manipulate DNA structural change …”
Section: Dynamic Dna Nanotechnologymentioning
confidence: 99%
“…There are also many other strategies to induce dynamic structural changes, including molecular recognition, such as aptamer binding, hybridization, and dehybridization of nucleic acid duplexes, environmental factors such as pH value, temperature, , light, , and ionic concentration, and enzymatic reactions to DNA strands, such as strand degradation, cleavage, ligation, and extension . Specifically designed DNA sequences can enable DNA structural changes regulated by metal ions or pH. , Base stacking between blunt ends of DNA helices is sensitive to metal ions and temperature and has also been utilized to manipulate DNA structural change …”
Section: Dynamic Dna Nanotechnologymentioning
confidence: 99%
“…73 In a recent work, Wang et al substituted the spacing region with a flexible and pH-sensitive i-motif sequence that could form a Cquadruplex structure at low pH. 74 The C-quadruplex formation resulted in a shortening of the distance between adjacent DNA origami units, but the original interunit distance could be recovered by increasing the pH and thus turning the Cquadruplex back to ssDNA counterparts. The i-motif was incorporated into the connector sequences used to link DNA origami units into a 3D lattice, and depending on whether the i-motif was part of the connector strand in 1D, 2D, or 3D, the lattice could rapidly and reversibly either switch between a simple cubic and simple tetragonal lattice (i-motif included in the connector strands for 1D or 2D) or shrink and expand (imotif included in all connector strands).…”
Section: Dynamic Lattice Reconfigurationmentioning
confidence: 99%
“…For example, it has been demonstrated that high salt concentration, ethanol and certain polymers may cause a shrinkage of the ssDNA region and thereby a contraction of the whole DNA origami lattice . In a recent work, Wang et al substituted the spacing region with a flexible and pH-sensitive i-motif sequence that could form a C-quadruplex structure at low pH . The C-quadruplex formation resulted in a shortening of the distance between adjacent DNA origami units, but the original interunit distance could be recovered by increasing the pH and thus turning the C-quadruplex back to ssDNA counterparts.…”
Section: Stimuli-induced Dynamics Of Dna Origami Latticesmentioning
confidence: 99%
“…Therefore, it is crucial to develop a reliable strategy to artificially synthesize dynamic crystals possessing nimble phase transition abilities. In the past decades, well-designed DNA strands, with considerable advances in organizing nano-objects, enabled the fabrication of highly ordered nanoparticle superlattices with various symmetries. Furthermore, it has been recently reported that several advancements have broken the single correspondence between materials and their underlying structures by allowing the construction of dynamic superlattices that can shift between duple or multiple isolated states using DNA units. However, it remains a huge challenge to customize a dynamic superlattice system that can freely shift among these states and further derive secondary phases between obtained states by rational control. Orthogonal integration of the environmentally responsive functional motifs into the different dimensions of a single superlattice stands as the key point of realizing dynamically reconfigurable DNA origami crystals.…”
Section: Introductionmentioning
confidence: 99%